RELATIONSHIP BETWEEN CULTURAL DIVERSITY, INTERPERSONAL CONFLICT, PERCEIVED SOCIAL DISTANCE AND PSYCHOLOGICAL DISTRESS: AN EMPIRICAL EVIDENCE FROM PUBLIC SECTORS BANKS OF QUETTA - Tayybah Safdar, Dr. Muhammad Shafiq, Sayyed Khawar Abbas, Asma Azhar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The growth of the cultural diversity has been increasing both internationally and domestically which as a result has affected the performance and the behaviour of the individuals in the workplace. Employees’ performance and attitudes are affected due to working with people who have different background; their values, norms, attitudes, etc. are completely change. The research, therefore, has established on the relationship between cultural diversity, interpersonal conflict, perceived social distance and psychological distress in the public banking sector of Quetta. The psychological distress was measured with the effect of the conflict and social distance among the bankers. Quantitative research method was applied, in which a sample size of 300 employees of public banks were selected. Data was collected through convenience sampling technique. For the analysis of the data IBM SPSS 21 was used. The study was supported by three hypotheses where all of them were accepted. The study was concluded that cultural diversity has an affirmative effect on interpersonal conflict. Likewise cultural diversity positively affects perceived social distance. Furthermore, it was concluded that interpersonal conflict and perceived social distance will have a positive affect on psychological distress. The study postulates that employees working in the diverse environment have to go through conflict and create social distance that gives rise to distress in the workplace.